Sistem Pengendali Buka Tutup Atap dan Blower Otomatis untuk Jemuran Menggunakan Mikrokontroler Arduino Berbasis Android - Supriyana Nugroho; Ibnu Mas’ud Himawan; Cicilia Puji Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2020)
Automatic control systems in the field of science and technology lately are developing rapidly. With the progress in the field of science and technology produce new innovations that develop towards better. Open and close roof and automatic blower system This system uses two inputs namely rain sensor and HC06 Bluetooth module as well as four outputs namely LCD output, servo motor, relay, and fan blower. Rain sensor is used to detect the presence of water spots, this sensor works with the principle of connecting between pcb lines that are exposed to water and then emits a signal that will be read by an analog port on Arduino Uno. The HC06 Bluetooth module is used to intermediate serial data from an Android smartphone to the Arduino Uno RX TX port. LCD to display the working condition of the device. Servo motors are used to open or close the roof. The relay is used as a bridge between the arduino uno and the fan blower, while the fan blower is used to dry the clothesline when the roof is closed.